Role of Plant Growth-Promoting Rhizobacteria (PGPR) and Bio-Control Agents (BCAs) in Crop Production - Sujata Kumari; Narender K. Bharat; Ashok K. Thakur (International Journal of Economic Plants)
The bioagents like Plant Growth Promoting Rhizobacteria (PGPR) and Biocontrol Agents (BCAs) play a crucial role in plant growth promotion, nutrient uptake and suppression of biotic and abiotic stresses. Different researchers have applied these bioagents by various means either through seed treatment or through soil application to prevent various plant diseases. Thus, these non-chemical environment friendly tools can be exploited to enhance crop production.